2014
DOI: 10.1158/1078-0432.ccr-14-0297
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Status of Key Cell-Cycle Regulators Such as CDKNA2/p16 and CCNA1 Correlates with Treatment Response to Doxorubicin and 5-Fluorouracil in Locally Advanced Breast Tumors

Abstract: Purpose: To explore alterations in gene promoter methylation as a potential cause of acquired drug resistance to doxorubicin or combined treatment with 5-fluorouracil and mitomycin C in human breast cancers.Experimental Design: Paired tumor samples from locally advanced breast cancer patients treated with doxorubicin and 5-fluorouracil-mitomycin C were used in the genome-wide DNA methylation analysis as discovery cohort. An enlarged cohort from the same two prospective studies as those in the discovery cohort … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 29 publications
2
44
0
Order By: Relevance
“…Bisulfite conversion and DNA methylation analysis using the Illumina Infinium HumanMethylation27 and HumanMethylation450 beadchip assays was carried out as previously described [32, 33]. Preprocessing and normalization involved steps of probe filtering, color bias correction, background subtraction and subset quantile normalization as previously described [34].…”
Section: Methodsmentioning
confidence: 99%
“…Bisulfite conversion and DNA methylation analysis using the Illumina Infinium HumanMethylation27 and HumanMethylation450 beadchip assays was carried out as previously described [32, 33]. Preprocessing and normalization involved steps of probe filtering, color bias correction, background subtraction and subset quantile normalization as previously described [34].…”
Section: Methodsmentioning
confidence: 99%
“…In a human lung cancer cell line, higher concentrations of 5-FU induced significant DNA hypermethylation 25 . In breast cancer locally advanced tumors, key cell cycle regulator genes were differentially methylated before and after combined treatment with 5-FU and mitomycin D 26 . These data suggest that 5-FU treatment may affect DNA methylation of peripheral blood leukocytes, through direct and indirect mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…5-Azacytidine was the first hypomethylating agent to be approved by the US Food and Drug Administration for the treatment of myelodysplastic syndrome,41 and subsequent studies further confirmed its anticancer effectiveness 42,43. Advanced studies have also demonstrated that the methylation status of cell cycle regulators is associated with the sensitivity of chemotherapeutic agents in breast cancer 44. From this perspective, hypomethylation of methylated CDKN2A using a hypomethylating agent might be a whole new approach to cervical cancer therapy.…”
Section: Discussionmentioning
confidence: 97%